Expression of bovine meat and milk factor in hepatocellular carcinoma and colorectal liver metastasis patients - Siqin, Sumen; Rahbari, Mohammad; Ernst, Claudia; Grewe, Imke; Gunst, Karin; Neßling, Michelle; Kaden, Sylvia; Richter, Karsten; Häfele, Lisa; Feuerbach, Lars; Krunic, Damir; Teßmer, Claudia; et al. (Journal of medical virology, 2025)
Bovine meat and milk factors (BMMFs) are plasmid-like DNA molecules isolated from cow's milk, meat, and human cancer tissues proposed to contribute to the development of specific types of cancer including colorectal cancer (CRC) and breast cancer based on chronic inflammation-associated indirect carcinogenesis. Chronic necro-inflammation of the liver poses a strong risk factor for the induction of hepatocellular carcinoma (HCC), which is associated with high intake of meat. Whether BMMFs contribute to HCC carcinogenesis or the development of colorectal liver metastasis (CRLM) remains unknown. Therefore, in this study, the presence of BMMFs was assessed in the liver of patients with viral and nonviral hepatitis-related HCC (n = 25), CRLM (14) and in healthy liver tissue from autopsy specimens (18) using monoclonal antibodies against the conserved BMMF Rep protein for immunohistochemistry, immunofluorescence detection, and immunoblotting. Rep was expressed in all tumor-distant and peritumor tissue specimens of HCC and CRLM patients and associated with CD68+ macrophages around portal triads. The number of Rep+CD68+cells was increased in HCC and CRLM patients compared to healthy liver tissue, which may indicate a link between BMMFs and tumor-associated chronic inflammation in the liver. Exclusively in viral hepatitis-linked HCC, Rep expression was also detected in the tumor. In addition, specifically in the liver of healthy individuals, we observed a well-defined gradient Rep expression in hepatocytes around the central veins. Altogether, these observations may indicate that the presence of BMMFs in the liver is associated with chronic inflammation and may represent a novel risk factor or surrogate marker for liver cancer.